Ibn Jarīr al-Ṭabarī and His Approach on the Tafsīr of the Qur’ān - Yasir Sulaiman Almuways (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2020)
This article talks about one of the greatest scholars of Tafsīr who was given the title of The Scholar of the Scholars (ʾImām al-ʾAʾimmah) and ʾImām al-Mufassirīn due to his significant contribution to all the fields of knowledge in Islam, especially in Tafsīr. Thus, in this article, we will cover his biography from birth to death from a historical point view. Also, this article will highlight his approach for the process of conducting the Tafsīr of the Qur’ān based on his book Tafsīr Jāmiʽ al-Bayān ʽan Tʾwīl Ᾱyi al-Qurʾān through a descriptive and an analytical methodological approach. This article results in significant facts about how Ibn Jarīr has been shaped in terms of his knowledge during his journey of seeking knowledge and how this has reflected on how he has presented his work of Tafsīr from which his methodological principles of Tafsīr have been extracted